Strategic positioning of navigation and communication technologies in Indonesia’s defence UAV ecosystem - Sinulingga, Wenly Andalenta; Wandebori, Harimukti; Prawiraatmadja, Widhyawan (Pusat P2M Politeknik Negeri Batam, 2026)
This study examines the strategic positioning of navigation and communication subsystems within Indonesia’s defence Unmanned Aerial Vehicle (UAV) ecosystem. Guided by the Industrial-Organization (I/O) model, the research integrates market analysis, external environment assessment, and internal capability alignment to develop positioning approaches for GPS-denied inertial navigation and small-form-factor satellite communication (SATCOM) technologies. A qualitative methodology was employed, combining semi-structured interviews with defense stakeholders and secondary sources from policy, industrial, and technical domains. The findings show that effective positioning depends on early engagement with the Ministry of Defense, the armed forces as end-users, and DEFEND ID state-owned enterprises, while also meeting localization and offset requirements. Drawing on Porter’s concept of needs-based positioning and applying the Strategy Diamond model, the study identifies arenas, vehicles, differentiators, staging, and economic logic as interdependent elements shaping market entry. The proposed three-phase roadmap, focused on stakeholder engagement, system integration, and local sustainment, supports Indonesia’s defense modernization priorities while enabling multinational firms to secure a sustainable market presence.